Expression and Role of PDK4 on Childhood Dyslipidemia and Lipid Metabolism in Hyperlipidemic Mice - Cai, Wenjuan; Wang, Xin; Deng, Qian; Gao, Jian; Chen, Yuqing (Hormone and Metabolic Research, 2023)
Hyperlipidemia is a common metabolic disorder that can lead to cardiovascular disease. PDK4 is a key enzyme that regulates glucose and fatty acid metabolism and homeostasis. The aim of this study is to explore the correlation between PDK4 expression and dyslipidemia in obese children, and to find new therapeutic targets for hyperlipidemia in children. The expression of PDK4 in serum was detected by qRT-PCR. Receiver operating characteristic curve was used to analyze the relationship between PDK4 and dyslipidemia. Upstream miRNAs of PDK4 were predicted by the database and verified by dual luciferase reporter gene assay and detected by qRT-PCR. The hyperlipidemia mouse model was established by high-fat diet (HFD) feeding, and the metabolic disorders of mice were detected. PDK4 is poorly expressed in the serum of obese children. The upstream of PDK4 may be inhibited by miR-107, miR-27a-3p, and miR-106b-5p, which are highly expressed in the serum of obese children. Overexpression of PDK4 improves lipid metabolism in HFD mice. miR-27a-3p silencing upregulates PDK4 to improve lipid metabolism. In conclusion, PDK4 has a diagnostic effect on dyslipidemia in children, while lipid metabolism in hyperlipidemic mice could be mitigated by upregulation of PDK4, which was inhibited by miR-107, miR-27a-3p and miR-106b-5p on upstream.
Keywords: dyslipidemia; hyperlipidemia; pyruvate dehydrogenase kinase 4; obese children; microRNA-27a-3p; microRNA-107